2009
DOI: 10.1002/apj.260
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing acidic methanolysis of poly(3‐hydroxyalkanoates) in gas chromatography analysis

Abstract: This work was undertaken to develop an improved gas chromatography (GC) analysis of poly (3-hydroxyalkanoate) (PHA) quantification method based on acidic methanolysis. This is achieved by investigating the kinetics of acidic hydrolysis of PHAs with sulfuric acid in the chloroform/aqueous solution to identify suitable hydrolytic pretreatment conditions for quantitative analysis of PHAs. The target parameters included sulfuric acid concentration, salt (NaCl) addition, kind of PHAs (commercial products of poly-3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 43 publications
(25 reference statements)
1
7
0
Order By: Relevance
“…Lo et al indicated that various molecular weights of PHB affect the thermal press application . A lower M w (such as 220,000 g/mol) cannot make a film using the isothermal press process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lo et al indicated that various molecular weights of PHB affect the thermal press application . A lower M w (such as 220,000 g/mol) cannot make a film using the isothermal press process.…”
Section: Resultsmentioning
confidence: 99%
“…In most cases, the thermal decompositions of PHAs polymers have been investigated using non‐isothermal techniques, such as using TGA in nitrogen. The PHB and PHBV backbones cleaved in a one‐stage process, in which the decomposing temperatures ranged from 190 to 300°C and 190 to 250°C, and the onset temperatures were 240°C and 210°C, respectively. Figure shows TGA thermograms of PHB and PHBV.…”
Section: Resultsmentioning
confidence: 99%
“…Following fermentation, centrifugation was used to separate the medium and the cells. Wet cells were separated using centrifugation at 5,000g for 10 min, washed by ethanol (20 mL) three times, and then dried to a constant weight in an oven at 55 • C. After drying, the purity of PHB was analysed using gas chromatograph, as reported in our previous work (Lo et al, 2009). Then, the dried sample was into a powder.…”
Section: Methodsmentioning
confidence: 99%
“…Following the procedure in Lo et al (2009) [33], an acidic methanolysis reaction was used to hydrolyze the polymeric chain and to convert the monomers into their methylated ester form. A PHA sample of each experiment was weighed for a mass between 2 and 5 mg and brought into a 5 mL reaction vial.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Thermal gravimetric analysis (TGA) [32] can be applied for a quick overview of these parameters when focusing on the degradation temperature of the produced PHA. Gas chromatography combined with mass spectrometry (GC-MS) is a more accurate technique that allows the investigation of the monomer concentration, composition and purity of the product [33]. Some studies made a parallel in between these techniques, showing that, even though different PHA content values were obtained by each method, there is a direct correlation between them [34].…”
Section: Introductionmentioning
confidence: 99%